О свободных колебаниях ортотропных конических оболочек переменной в двух направлениях толщины - Григоренко, А.Я.; Мальцев, С.А. (Видавничий дім "Академперіодика" НАН України, 2009)
Пропонується чисельно-аналiтичний пiдхiд для дослiдження вiльних коливань тонких конiчних ортотропних оболонок змiнної товщини, який базується на сплайн-апроксимацiї невiдомих функцiй. Розрахунки виконано для рiзних типiв граничних умов. Дослiджено вплив змiнної товщини на характер поведiнки динамiчних характеристик. The paper considers free vibrations of thin orthotropic conical shells with variable thickness basing on the method of spline-approximation of unknown functions. Calculations were carried out for different types of boundary conditions. The influence of the variable thickness of shells on free vibrations is studied. Free vibrations of shells with constant and variable thicknesses are compared.